2012
DOI: 10.1021/ef3012867
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Silicon in Vegetable Oil and Biodiesel by High-Resolution Continuum Source Flame Atomic Absorption Spectrometry Using Sample Dilution with Xylene

Abstract: In this paper, a simple procedure for the determination of Si in vegetable oils and biodiesel of different origins by high-resolution continuum source flame atomic absorption spectrometry is proposed. Samples were diluted with xylene, and external calibration was performed with calibration solutions prepared with xylene and mineral base oil used for viscosity matching. The accuracy was assessed using recovery tests and comparing the results for a set of vegetable oils and biodiesel to those determined by induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is reasonable to argue that the Hg levels found in fossil diesel principally originate from the crude oil or petroleum. In turn, the Hg content in crude oil may vary considerably according to the nature of the original organic matter from place to place and how its exploitation/exploration is done. ,, On the other hand, Hg in biodiesel is rather a trace or ultratrace contaminant, which may come from its incorporation during plant growth, from fertilizers and/or soil contamination or incorporation during fuel storage and/or transportation. For instance, Aranda et al found Hg at 2.6–3.3 μg kg –1 and Aranda et al detected 23.2 μg kg –1 in biodiesel samples (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…It is reasonable to argue that the Hg levels found in fossil diesel principally originate from the crude oil or petroleum. In turn, the Hg content in crude oil may vary considerably according to the nature of the original organic matter from place to place and how its exploitation/exploration is done. ,, On the other hand, Hg in biodiesel is rather a trace or ultratrace contaminant, which may come from its incorporation during plant growth, from fertilizers and/or soil contamination or incorporation during fuel storage and/or transportation. For instance, Aranda et al found Hg at 2.6–3.3 μg kg –1 and Aranda et al detected 23.2 μg kg –1 in biodiesel samples (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the abrasive action of the inorganic silicon forms and deposition of silicon sediments on engines, boilers, sensors, and catalysts, some threshold Si concentrations have been established, for example, at a level below 0.01 mg kg –1 for reforming feed, 25–60 mg kg –1 for various types of marine fuels, and 3 mg kg −1 for liquid biohydrocarbons . In Brazil, a sum of Si and Al in diesel oil should be below 80 mg kg −1 and a limit of 5 mg kg −1 of Si in B100 (biodiesel) has been considered . With the exception of Brazil, the Si content is not controlled in automotive and aviation fuels. ,,, However, according to Worldwide Fuel Charter, the concentration of Si in all types of gasoline and in most types of diesel fuel should be below 1 mg kg –1 .…”
Section: Introductionmentioning
confidence: 99%
“…33 In Brazil, a sum of Si and Al in diesel oil should be below 80 mg kg −134 and a limit of 5 mg kg −1 of Si in B100 (biodiesel) has been considered. 34 With the exception of Brazil, the Si content is not controlled in automotive and aviation fuels. 22,23,25,26 However, according to Worldwide Fuel Charter, 35 the concentration of Si in all types of gasoline and in most types of diesel fuel should be below 1 mg kg −1 .…”
Section: Introductionmentioning
confidence: 99%